Extrinsic and intrinsic rewards that influencing employees’ motivation in Syarikat Faiza Sdn Bhd / Suhaila Wahid and Hamizah Mohd Tohir - Wahid, Suhaila; Mohd Tohir, Hamizah (2015)
This paper objective to study extrinsic and intrinsic rewards that influencing employee’s motivation in Syarikat Faiza Sdn Bhd. The independent variable that involved in this study are payment and promotion for extrinsic rewards, recognition and job security for intrinsic rewards. For this research paper were focused on employee has been worked at Syarikat Faiza Sdn Bhd. 92 questionnaire were distributed to employees. The questionnaires were used to obtain and collected the data from the respondent. Stratified random sampling has been used in this study as a sampling technique. The researcher used SPSS program version 20.0 where the researcher has used reliability analysis, frequency analysis, correlation analysis and regression analysis. In the end of this paper, the researcher has provided several recommendations for Syarikat Faiza Sdn Bhd to increase the employee’s motivation and future researcher to improve their research paper.